2014
DOI: 10.1002/jbm.a.35240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium‐modified titanium implant surfaces on platelet activation, clot formation, and osseointegration

Abstract: The clinical success of load bearing dental and orthopedic implants relies on adequate osseointegration. Because of its favorable properties, titanium is generally considered as the material of choice. Following implant placement, titanium surfaces establish an ionic equilibrium with the surrounding tissues in which calcium plays major roles. Calcium is a cofactor of the coagulation cascade that mediates plasma protein adsorption and intervenes in a number of other intra and extracellular processes relevant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 46 publications
2
67
0
12
Order By: Relevance
“…We have reported previously that such diffusion accounts for around 70 % of the total surface calcium that it promotes surface-bound coagulation and platelet activation in the microenvironment of the implant surface. [6] Although here we have used a different technique (ICP) and a different substrate geometry (discs instead of implants), in this work we have reached a comparable result (66 %). The difference is presumably due to the duration of the sustained release that ensues.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We have reported previously that such diffusion accounts for around 70 % of the total surface calcium that it promotes surface-bound coagulation and platelet activation in the microenvironment of the implant surface. [6] Although here we have used a different technique (ICP) and a different substrate geometry (discs instead of implants), in this work we have reached a comparable result (66 %). The difference is presumably due to the duration of the sustained release that ensues.…”
Section: Discussionsupporting
confidence: 83%
“…The values obtained were similar to those reported previously. [6] When no further chemical modification was applied (NoCa 2+ ), samples were ß-ray sterilized and stored until use. Unless otherwise stated, calcium-ion modified surfaces (Ca 2+ ) were prepared by sonication during 30 s in a bath containing 5 wt.…”
Section: Substrate Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of chemical methods modify not only topography, but also other surface features such as chemical composition, [25] wettability, [26] crystallinity, [27] and adsorption ability. [28] These surface observables can also modulate cell behavior [27,[29][30][31] (for more information about surface modification strategies and cellular recognition of these surfaces see the review papers [32,33] ) and it is difficult to distinguish which factor leads to the observed cell response.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the different minerals that were studied, researchers found that calcium is an especially beneficial surface-enriching molecule because it has been proven to be very osteo-inductive and is very effective at encouraging bone formation around the implants. Anitua et al demonstrated that the incorporation of calcium ions onto the surfaces of biomaterials promoted near bone growth in rabbits' femora [12]. Similarly, other animal studies also confirmed the beneficial effects of calcium, such as improved bone formations in rat femora, increased healing of intrabony defects in dog mandibles, and enhanced resistance to dislodgement in rabbit tibia [13][14][15].…”
Section: Introductionmentioning
confidence: 97%